Role of servitization in transitioning from scarcity to abundance paradigm - Hora, Manpreet (Frontiers in Research Metrics and Analytics, 2022)
Servitization refers to firms, rather than just selling the product, sell “outcome-as-a-service” (for example software-as-a-service). This phenomenon, specifically with the digitization of things utilizing cloud computing platforms and cyber-physical systems has for several products transformed “the state of scarcity into that of abundance”. In this chapter, we focus on two objectives and examine (i) how servitization has enabled companies such as Netflix to disrupt industries. transitioning from offering products that were inherently finite to delivering services and making them more abundant, and (ii) as firms embark upon servitization and value propositions are not emanating or related to scarcity, then a second research question naturally emerges: what are the value propositions for consumers when the paradigm shifts from ownership to usership?